Montelukast: risk of mental disorders vs. efficacy–a meta-analysis - Sobczak, Marharyta; Pawliczak, Rafał (Frontiers in Pharmacology, 2025)
BackgroundMontelukast, a selective leukotriene receptor antagonist, is widely used in the treatment of bronchial asthma and allergic rhinitis (AR). Although it is a well-tolerated drug, there are reports of possible central nervous system side effects, including, for example, mood changes and suicidal thoughts. Therefore, we conducted a meta-analysis to test the effects of montelukast on the mental health of patients taking montelukast and to test its effectiveness in treating asthma and AR.MethodsPubMed, Web of Science, and the Cochrane Central Register of Controlled Trials databases were searched to find articles of control-compared randomized clinical trials, which investigated the efficacy of montelukast treatment as well as articles about mental disorders after this treatment. The relative risk with 95% confidence interval (CI) and the standardized mean difference with 95% CI were calculated to compare the effect. A random effects model was used to calculate effect sizes.ResultsOur meta-analysis was based on 4 studies (mental health analysis) and 19 studies (efficacy analysis). We indicated that montelukast treatment was associated with a higher risk of anxiety by 11% (RR = 1.11; 95% CI [1.06; 1.16]; p < 0.0001, I2 = 0%) without differences between subgroups. Meta-analysis showed the different efficacy of montelukast against asthma and AR symptoms in comparison to placebo and other drugs.ConclusionIn terms of treating asthma and allergic rhinitis, montelukast shows comparable efficacy to other drugs, such as inhaled corticosteroids or second-generation antihistamines. Furthermore, montelukast was associated with a modestly increased risk of anxiety, while no consistent evidence was found for an increased risk of depression or suicidal behaviors, considering the limited data.